On the 25th anniversary of the publication of the World Atlas of Snow and Ice Resources - V. M. Kotlyakov (Лëд и снег)
The World Atlas of Snow and Ice Resources was compiled from 1976 to 1993 by a team of 300people under the auspices of the USSR Academy of Sciences and UNESCO. The relationship within the large group of authors was governed by the Atlas Statute, approved by the Editorial Board. A special program for Soviet cosmonauts was created to collect materials in poorly studied high-altitude glacial areas. The maps prepared for the Atlas were discussed annually at special seminars, and a special trip of section editors and leading map authors to the high-mountain glaciers of the Pamirs was made to gain experience in map-making. Compilation work continued from 1976 to1993. The layout of the Atlas was prepared and the maps were printed in Minsk and Kiev. The Atlas was published in 1997 and in 2001 it was awarded the State Prize of Russia in the ﬁeld of science and technology. 18years aﬅer its publication, an electronic version of the atlas was prepared. The World Atlas of Snow and Ice Resources is an outstanding achievement of modern geography, cartography and glaciology.